Analytical determination of compounds released during pyrolysis, smoldering, and combustion experiments with insulation materials from renewable resources. (19th March 2022) - Wichmann, Hubertus; Kolb, Marit; Bulutcu, Deniz; Kolb, Torsten; Zehfuß, Jochen
Summary: Obviously, the use of insulation materials from renewable resources in buildings could provide benefits regarding environmental protection and sustainable management. Nevertheless, their market share in Germany is estimated to be about 7% because of a partial lack of knowledge about their properties, and therefore, of construction certifications. This work was intended to close a knowledge gap concerning emissions during pyrolysis, smoldering, and combustion of commercial insulating materials made from wood, cellulose, meadow grass, hemp, jute, cork, and seaweed as well as polystyrene for comparison reasons. Laboratory‐scale experiments were conducted and the measurement of thermal decomposition products was done with gas chromatography combined with mass spectrometry (GC/MS). It was realized that almost all the products could be assigned to the following eight substance classes: carbohydrates, aldehydes/ketones, carbonic acids/esters, substituted phenols, furans, aliphatic hydrocarbons, substituted benzenes, and polycyclic aromatic hydrocarbons. Substance spectra were generated that showed certain conformities, especially between the insulating materials made from wood, cellulose, and meadow grass as well as hemp and jute. Comparisons of the sum of peak areas in the GC/MS‐chromatograms provided indications of the relative extent of thermal decomposition product emissions. Calculations according to (∑peak areas renewable material )/(∑peak areas polystyrene ) revealed factors between 0.18 (wood, cork) and 0.028 (meadow grass). In the thermal emissions, defined hazardous substances or substance groups were frequently measured. These were included in a toxicity evaluation by which, inter alia, advantages of the natural products compared to polystyrene could be demonstrated.